Tourism as a means of developing isolated regions: Defining the Image of a tourism destination from the demand and supply side - Vassilis Angelis; Ioanna Tsoka; Katerina Dimaki (European Regional Science Association (ERSA), 2011)
The development of a region is subject to its ability to attract business activities and the right blend of people to run them. This ability depends on a number of factors and previous research as well as historical evidence show that the region's location is a key factor among them. Hence, isolated regions are at a disadvantage in attracting business activities adversely affected by geographical discontinuity and they should focus on specific activities. Tourism is such an activity for which geographical discontinuity is not a barrier, but on the contrary it may be an advantage. Hence, tourism may act as a driving force for the development of isolated regions. On the basis of the above, a region may become a competitive tourism destination, provided of course that it possesses a number of characteristics. An overview of the literature reveals that most of the studies referring to tourism destinations focus on the attraction of tourists, i.e. the demand side and very few on the attraction of tourism industry, i.e. the supply side. Our objective in this paper is to identify the factors (both supply and demand) affecting a tourism destination, suggest ways of measuring them and define the Image of the tourism destination, i.e. a measure of its attractiveness, as a function of those factors. Finally, the theoretical findings will be applied to a number of tourism destinations.
Keywords: 330; Regional development; isolated regions; tourism; tourism destination; Image of a tourism destination